Translating evidence into policy: opinions and insights of Health Researchers and Policymakers in Nepal - Biplav Babu Tiwari; Anusha Ban; Sony Gurung; Khem Bahadur Karki (BMC, 2021)
Abstract Background The Evidence-Based Policymaking (EBP) process in Nepal is rife with poor practices where often policymakers are portrayed as perpetrators for such practices. However, we need to think of the EBP as a two-sided coin where both research pull and research push play equally significant roles. This study aimed to assess the perception of Nepalese health policymakers and researchers on EBP and identify appropriate mechanisms to integrate evidence into policies. Methods Following the constructivist philosophical paradigm, qualitative research design was used in the study with the grounded theory approach. Purposive sampling was performed, and the 12 in-depth interviews were conducted, where number of interviews was finalized using saturation theory. All interviews were audio-recorded, transcribed, translated to English, coded line by line, and then developed into themes. Thematic analysis technique was used to manually analyze the data. Results Study participants highlighted that evidence is being utilized during policy formulation but not in the amount it should be, with a preference for anecdotal evidence further reducing the chance. Apart from these barriers, poor credibility of information obtained, poorly targeted dissemination, inadequate policy-based researches, and policymakers and researchers operating within the spheres of their own with a feeble link to channel the flow of information between them were identified by participants. On the other hand, the publication of one-pager research brief, conduction of nationally representative surveys especially quantitative studies, the practice of cost-effectiveness study, and policymaker's involvement during the research were some facilitators identified. Conclusions Moreover, the study accentuates that better communication strategies such as the establishment of formal forums with policymakers and researchers, better-targeted dissemination, and identification of priority areas have wide potential to promote a unified front of health policymakers and researchers for EBP.